Changing primary care capacity in Canada: protocol for a cross-provincial mixed methods study - Erin Wilson; Agnes Grudniewicz; Antoine Sauré; Ian Scott; Alan Katz; M Ruth Lavergne; Claire Johnson; David Rudoler; Lindsay Hedden; Adrian MacKenzie; Rita McCracken; Ruth Martin-Misener; et al. (BMJ Open)
Introduction Despite having more family physicians (FPs) and nurse practitioners (NPs) per capita than ever before in Canada, there is a clear gap between population primary care needs and system capacity. Primary care needs may be shaped by population ageing, increasing clinical and social complexity and growing service intensity. System capacity may be shaped by falling practice volumes, increasing administrative workload, changing clinician demographics and new health system roles (eg, hospitalist and focused practices). These changing factors could contribute to reduced patient access to primary care, worsened health inequities and stress and overwork among primary care clinicians. Workforce planning tools used in most countries do not adequately consider these factors. Our study will identify and explore factors shaping population service use and system capacity over time and develop planning tools to estimate future primary care needs and capacity.Methods and analysis We will interview FPs and NPs about factors shaping workload, including patient characteristics, practice expectations and system context. This will inform analysis of administrative data to describe factors shaping primary care need (patient demographics, clinical and social complexity, service intensity) and capacity (provider supply, demographics, service volume, roles) over a 20-year period from 2004/2005 to 2023/2024. Qualitative and quantitative findings will inform analytical models that project and compare need and capacity under stakeholder-informed scenarios. The study includes the Canadian provinces of British Columbia, Manitoba, New Brunswick and Nova Scotia, provinces with varied policy and population contexts and complementary administrative health data.Ethics and dissemination Research ethics board (REB) approval for the qualitative study has been provided by Research Ethics BC, with subsequent approvals from Horizon Health Network, Nova Scotia Health, University of Manitoba and University of Ottawa. REB approval for analysis of linked administrative data was obtained from the Nova Scotia Health REB, Research Ethics BC, University of Manitoba and University of New Brunswick. Our findings will support primary care capacity planning to equitably meet the needs of a growing and ageing population.